Section 15: How Indigenous Use of the Charter Tool is About Returning to Respect Not Creating Equity - Major, Rebecca (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
Some Canadians view the concept of freedom in relation to government involvement differently, particularly when government presence is seen as oppressive or colonizing. While Indigenous communities in Canada may not always view the current governance structure as reflective of their own traditions, they recognize the necessity of using it to navigate challenges. Indigenous groups utilize section 15 to address inequalities that stem from historical colonialism, seeking to restore balance in a manner consistent with pre-colonial ideals. Prior to the repatriation of the constitution, attempts to address equity issues through the legal system were often met with limited success, prompting Indigenous women in Canada to take their gender equity concerns to the United Nations with respect to the Indian Act. Following the repatriation, section 15 has provided a platform for Indigenous peoples to address policies and laws that unfairly disadvantage certain groups in comparison to others, thereby promoting fair treatment from the government. This discussion aims to explore how Indigenous communities utilize Section 15 as a tool to address issues of unequal treatment and advocate for equity that aligns with traditional pre-colonial values.